2018
DOI: 10.1038/s41426-018-0206-y
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiological investigation of HAdV-4 infection among healthy adults in China and in Sierra Leone, West Africa

Abstract: An apparent increase in the frequency of human adenovirus type 4 (HAdV-4) infections among general populations has been observed over the past 10 years. However, available epidemiological data that may reflect previous viral circulation and assist in predicting potential outbreaks are sparse, particularly in mainland China and Africa. In this study, a convenient neutralization assay for use in the surveillance of historical HAdV-4 infections was established based on a recombinant luciferase-expressing virus. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(25 citation statements)
references
References 38 publications
0
25
0
Order By: Relevance
“…In non-captive environments, a survey of human sera that tested positive for antibodies against SAdVs may be paired with a sub-Saharan Africa dataset that reported a PCR-based survey of nonhuman primates to support the hypothesis that cross-species transmissions occur between humans and non-human primates (Xiang et al, 2006;Wevers et al, 2011). Additional reports of cross-species transmission of AdVs include sequence data and/or sero-neutralization data (Ersching et al, 2010;Pauly et al, 2015;Hoppe et al, 2015a;Wang et al, 2018). Again, the importance of these reports is two-fold.…”
Section: Discussionmentioning
confidence: 99%
“…In non-captive environments, a survey of human sera that tested positive for antibodies against SAdVs may be paired with a sub-Saharan Africa dataset that reported a PCR-based survey of nonhuman primates to support the hypothesis that cross-species transmissions occur between humans and non-human primates (Xiang et al, 2006;Wevers et al, 2011). Additional reports of cross-species transmission of AdVs include sequence data and/or sero-neutralization data (Ersching et al, 2010;Pauly et al, 2015;Hoppe et al, 2015a;Wang et al, 2018). Again, the importance of these reports is two-fold.…”
Section: Discussionmentioning
confidence: 99%
“…Upon its discovery in the 1950s [15], HAdV-E4 was largely considered restricted to and controlled by vaccine in the US military population, with rare detections among civilians, such as school children in the Netherlands in 1958 [16], users of a private swimming pool in the USA in 1977 [17], and conjunctivitis patients in Japan in 1979 [18]. More recently, surveillance for HAdV has improved, and evidence of HAdV-E4 infections among civilian populations in the USA, Italy, West Africa, China, Hong Kong, Taiwan, India, Malaysia, and Singapore have been increasingly reported [8,[19][20][21][22][23][24][25][26][27][28]. Due to the historical lack of HAdV genotyping surveillance, it is unknown whether HAdV-E4 is a new or re-emerging pathogen in SEA.…”
mentioning
confidence: 99%
“…Firstly, damage to the airway mucosa after Adv infection and the release of in ammatory mediators can cause bronchial and bronchioles mucosal edema, congestion, necrosis and shedding, necrotic obstruction of the lumen, and bronchial wall edema and thickening, resulting in vasospasm and muscle contraction. Because airway epithelial cells are damaged, its defence capacity is reduced, resulting in allergens invading the airway more easily (14), FAS/FASL expression to promote apoptosis. In the airways of atopic children, damaged neurons in the airway epithelia are exposed, increasing the airway sensitivity (23), and leading to more serious epithelial injury, thus making patients more susceptible to wheezing.…”
Section: Discussionmentioning
confidence: 99%
“…We are particularly addressing the question of why do some children experience severe symptoms and why do they have a poor prognosis. In recent years, most clinical studies have focused on virus typing (13,14,15), but few studies have assessed the risk factors associated with a poor prognosis. Previous regional studies in Singapore have shown that an Adv type 7 infection, a severe infection requiring invasive or non-invasive ventilation, and a family or personal history of asthma were risk factors for respiratory complications (16).…”
Section: Introductionmentioning
confidence: 99%